Achieving Service Excellence - Chang, C. M (Business Expert Press, 2014)
Ebook from IG Library ; As the service sectors play an increasingly important role in all economies worldwide, service executives and professionals are well advised to recognize two main pathways to achieving sustainable success in services. The first path requires enhancing the strategic differentiation and operational excellence of their service enterprises; the second requires that these executives and their employees develop the knowledge and skills needed to achieve such success. Specifically, this book discusses actionable methodologies needed to generate creative ideas, including deciding on which ones to pursue; on how to justify projects financially; on how to manage the development projects for innovative services; and on how to reach out to customers and offer them superior service support. The book will illustrate how operational excellence can be achieved by emphasizing the importance of standardizing work processes. It will demonstrate how quality can be enhanced and time-to-market can be reduced through a variety of methods including the application of tools (such as Lean Six Sigma, Value stream mapping, quality assurance, FMEA, web-based enablers and SOA-based emerging productivity tools), the incorporation of emerging technologies into the workflow and, with reference to the Profit Chain Model, the retraining of staff, with a goal of increasing their productivity, by adopting and constantly improving upon known best practices. This book summarizes the key skills and knowledge in a Three Decker framework comprised of engineering management, business management and service leadership, cumulating in an actionable Take Charge model. After having studied this book, service professionals and executives will know how to apply the actionable methodologies outlined herein to maximize their contributions in achieving sustainable success for their service employers.